Empty Follicle or Not? A Case Report - Çalışkan, Eray; Yalçınkaya, Ender (Gynecology Obstetrics & Reproductive Medicine, 2010)
Empty follicle syndrome is characterized by retrieving no oocytes in despite of achieving multiple follicle development in an IVF cycle. We report a case having a presumed empty follicle syndrome at 36th hour of human chorionic gonadotrophin (βhcg) administration and rescued by a second oocyte pick-up procedure performed at 42nd hour, without the need of a second dose of the drug. Intrauterine transfer of three good quality embryos resulted in a singleton pregnancy which ended with a healthy girl.